Design of Mononuclear Ruthenium Catalysts for Low‐Overpotential Water Oxidation. Issue 2 (16th October 2014) - Okamura, Masaya; Masaoka, Shigeyuki
Abstract Water oxidation is a key reaction in natural photosynthesis and in many schemes for artificial photosynthesis. Inspired by energy challenges and the emerging understanding of photosystem II, the development of artificial molecular catalysts for water oxidation has become a highly active area of research in recent years. In this Focus Review, we describe recent achievements in the development of single‐site ruthenium catalysts for water oxidation with a particular focus on the overpotential of water oxidation. First, we introduce the general scheme to access the high‐valent ruthenium–oxo species, the key species of the water‐oxidation reaction. Next, the mechanisms of the OO bond formation from the active ruthenium–oxo species are described. We then discuss strategies to decrease the onset potentials of the water‐oxidation reaction. We hope this Focus Review will contribute to the further development of efficient catalysts toward sustainable energy‐conversion systems.